When Blended Learning is Forced in the Amid of Covid-19: What Happen on EFL Learners’ Speaking Anxiety? - Sumarsono, Dedi; Haryadi, Haryadi; Bagis, Abdul Kadir (JOLLT Journal of Languages and Language Teaching, 2021)
The existence of Covid-19 has forced the migration of the teaching and learning paradigm from face to face interaction to online learning and to the combination of both known as blended learning. Blended learning is believed to provide opportunity for students to interact with each other with anxiety put at the lowest. This research was aimed to know 1) to what extent is the EFL Learners’ anxiety influenced by blended learning approach in this covid-19 pandemic?; 2) What factors contribute to student’ anxiety during Speaking activities in class in the Covid -19 age?. Mix research method was employed in this study as the data was analyzed both quantitatively and qualitatively. This study was conducted at second semester students of English department at Mandalika University of Education. The findings show that most students were anxious when communicating with each other. Factors like lack of confidence and fear of making mistakes, lack of vocabulary, low English proficiency, lack of practice, fear of being unable to follow and understand others were the primary causes of their anxiety.